Atrial myocyte-derived exosomal microRNA contributes to atrial fibrosis in atrial fibrillation - Hongting Hao; Sen Yan; Xinbo Zhao; Xuejie Han; Ning Fang; Yun Zhang; Chenguang Dai; Wenpeng Li; Hui Yu; Yunlong Gao; Dingyu Wang; Qiang Gao; et al. (Journal of Translational Medicine, 2022)
Abstract Background Atrial fibrosis plays a critical role in the development of atrial fibrillation (AF). Exosomes are a promising cell-free therapeutic approach for the treatment of AF. The purposes of this study were to explore the mechanisms by which exosomes derived from atrial myocytes regulate atrial remodeling and to determine whether their manipulation facilitates the therapeutic modulation of potential fibrotic abnormalities during AF. Methods We isolated exosomes from atrial myocytes and patient serum, and microRNA (miRNA) sequencing was used to analyze exosomal miRNAs in exosomes derived from atrial myocytes and patient serum. mRNA sequencing and bioinformatics analyses corroborated the key genes that were direct targets of miR-210-3p. Results The miRNA sequencing analysis identified that miR-210-3p expression was significantly increased in exosomes from tachypacing atrial myocytes and serum from patients with AF. In vitro, the miR-210-3p inhibitor reversed tachypacing-induced proliferation and collagen synthesis in atrial fibroblasts. Accordingly, miR-210-3p knock out (KO) reduced the incidence of AF and ameliorated atrial fibrosis induced by Ang II. The mRNA sequencing analysis and dual-luciferase reporter assay showed that glycerol-3-phosphate dehydrogenase 1-like (GPD1L) is a potential target gene of miR-210-3p. The functional analysis suggested that GPD1L regulated atrial fibrosis via the PI3K/AKT signaling pathway. In addition, silencing GPD1L in atrial fibroblasts induced cell proliferation, and these effects were reversed by a PI3K inhibitor (LY294002). Conclusions Atrial myocyte-derived exosomal miR-210-3p promoted cell proliferation and collagen synthesis by inhibiting GPD1L in atrial fibroblasts. Preventing pathological crosstalk between atrial myocytes and fibroblasts may be a novel target to ameliorate atrial fibrosis in patients with AF. Graphical Abstract